Global Epidemiology of HIV/AIDS: A Resurgence in North America and Europe - Govender, Romona D.; Hashim, Muhammad Jawad; Khan, Moien AB; Mustafa, Halla; Khan, Gulfaraz (Journal of Epidemiology and Global Health, 2021)
We aimed to assess global trends in Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) and evaluate progress toward eradication since the inception of the pandemic. Data were extracted from the Global Burden of Disease 2019 update and the UNAIDS Data 2019. The datasets included annual figures from 1990 to 2019 for HIV/AIDS in 204 countries and all world regions. We analyzed rates and trends for prevalence, incidence, mortality and disability adjusted life years. Analysis of age and gender distribution in different regions was used to assess demographic changes. Forecasting was used to estimate disease burden up to 2040. Although many countries have witnessed a decrease in the incidence, for Russia, Ukraine, Portugal, Brazil, Spain and the United States, the rates of new cases are rising since 2010. This trend is present even in age-standardized analysis, indicating a rise in excess of population growth. Over 0.5% of the world’s population is infected. About 5000 new infections occur daily, of which 500 are children. Mortality rates are falling globally; currently at 11 deaths per 100,000 population, forecasted to decrease to 8.5 deaths by 2040. Prevalence continues to increase, with South Africa, Nigeria, Mozambique, India, Kenya and the United States having the highest burden. The total number as well as the rates of new HIV infections are rising every year in Europe, South America, North America and other regions over the last decade. Maternal-to-child transmission continues at high rates despite effective preventive regimens. There is an urgent need to develop programs to curb the rising incidence of HIV.